EPR and Magnetic Studies of a Carboxylate-Bridged Dinuclear Copper(II) Compound: [Cu2(flu)4(dmf)2] - Nascimento, Otaciro R. (2011)
We report magnetic and EPR (electron paramagnetic resonance) spectroscopy studies of [Cu2(flu)4(dmf)2] (flu = flufenamate and dmf = dimethylformamide), which has CuII ions in tetracarboxylate "paddle wheel" dinuclear units. Susceptibility measurements at 10 < T < 275 K allowed the evaluation of an antiferromagnetic intradinuclear exchange coupling J0 = -294 ± 5 cm-1 between CuII ions (Hex = "J0 S1·S2). EPR experiments at 300 K in powder and single-crystals at 9.5 and 34.4 GHz indicated g// = 2.373, g⊥ = 2.073 and zero field splitting parameters D = (-0.334 ± 0.001) cm"1 and E ca. 0. EPR signal intensity measurements at X-band in the range 4 < T < 295 K indicated that J0 = "283 ± 5 cm"1. A higher limit |J´| < 5×10-3 cm-1 for the interdinuclear exchange coupling between neighbor units at ca.14.24 Å was estimated from the angular variation of the single crystal spectra around the magic angles. The results are discussed in terms of the structure of the dinuclear unit and the bridges connecting CuII ions and compared with values reported for similar compounds.